Evaluation of morphometry in extrahepatic bile ducts in preoperative and postoperative periods in diabetic and non - diabetic patients with cholelithiasis - Karataş, Turgay; Özbağ, Davut; Ogeturk, Murat; Demirtas, Gokhan; Şenol, Deniz; Çevirgen, Furkan; Kanlioz, Murat (My University, 2020)
Aim: The aim of this study was to find out and to compare the effect of cholecystectomy performed due to gallstone on theextrahepatic bile ducts morphometry in diabetic and non-diabetic patients.Material and Methods: Three groups consisting of a total of 120 individuals. Diabetic patients with cholelithiasis (DC group) consistedof 40 person, non-diabetic patients with cholelithiasis (N-DC group) consisted of 40 person and healthy group (H group) consistedof 40 person. Laparoscopic cholecystectomy was performed on individuals with cholelithiasis.DHC (ductus hepaticus communis) diameter was measured below hepatic canal bifurcation from mucosa to mucosa byultrasonography. The measurements were conducted in preoperative period and in the third and sixth postoperative months.Results: There were no significant differences between DC and N-DC groups in terms of DHC diameters in preoperative period andpostoperative third and sixth months. In both DC and N-DC groups, DHC diameters in postoperative third and sixth months werefound to show a small but statistically significant increase.Conclusion: This study showed a small but statistically significant dilatation in DHC following cholecystectomy. In addition, nostatistically significant difference was found between DC and N-DC groups in terms of post- cholecystectomy DHC dilatation.
Keywords: Genel ve Dahili Tıp